PENYULUHAN STRATEGI MENABUNG DAN INVESTASI UNTUK GEN Z RUMAH TAHFIDZ DI PERUMAHAN BATAN INDAH - Hasanah, Neneng; Purnomo, Endri; Risthi, Alyssa (Publika Citra Media, 2025)
Saving is a crucial first step in managing personal finances. In addition, investment is a smart way to grow wealth over time. To implement saving and investment activities for generation Z, Pamulang University Lecturers were moved to provide education and understanding related to this through Community Service (PKM) activities. This service aims to provide an understanding of the importance of saving and investing among generation Z who are at the Tahfidz House in Batan Indah Housing. With the increasing development of technology and access to information, this generation has the potential to manage finances better. This activity was carried out offline, namely by providing materials and discussions related to saving and investment strategies. This activity had a positive impact on participants, by increasing their discipline in managing their personal finances for a better future. The results of this activity showed an increase in participants' knowledge and awareness of financial management.